Facial Nerve Morbidity after Superficial Parotidectomy in the Absence of Nerve Conductor: A Cross-Sectional Study from a Tertiary Centre in Pakistan - Fazila Hashmi, Mushtaq Ahmed Abbasi, Muhammad Akbar, Salman Majeed Chaudhry, Sohail Yousif Arain, Samar Ghufran, Mehvish Adeel Dhahri, Adeel Abbas Dhahri, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: After superficial parotidectomy, the incidence of facial nerve injury for pleomorphic adenoma of the parotid gland remains the topic of interest despite different techniques to identify the nerve during surgery. We aim to evaluate the incidence of facial nerve injury in patients undergoing superficial parotidectomy without a nerve conductor. Material and Methods: After calculating the sample size, 101 patients, irrespective of age and gender, were included in this cross-sectional study at the Department of Surgery, for nine years, from 1st January 2012. The primary outcome was the incidence of temporary or permanent facial nerve injury with a follow-up period of 12 months. The data was calculated using SPSS version 23, where mean and standard deviation were calculated for continuous variables, and frequencies were calculated for categorical data. Results: Facial nerve injury was evident in 16/101 (15.8%) patients. Among these, the main truck of facial nerve was involved in 6(5.9%), temporary loss of function in 4(4.0%) and permanent injury in 2(2.0%). The most common branch of facial nerve affected was the marginal mandibular nerve (6, 5.9%), of which 4(4.0%) had a permanent loss. Additionally, four (4.0%) patients developed salivary fistula, whereas 2% developed Frey’s syndrome. Conclusion: Facial nerve injury should be clearly explained, in the consent, to the patient for a medicolegal purpose. Where the nerve stimulator is not available, identification of the proposed anatomical landmarks allows a safe recognition of the facial nerve Keywords: Pleomorphic adenoma, facial nerve, facial nerve injury, superficial parotidectomy